Analytical solution for the effect of anisotropic layers/interlayers on an elastic multi-layered medium subjected to moving load. (1st November 2019) - You, Lingyun; Yan, Kezhen; Shi, Tingwei; Man, Jianhong; Liu, Nengyuan
Abstract: The intent of this study was to develop an analytical solution for the mechanical behaviors associated with a three-dimensional anisotropic multi-layered medium when it is subjected to a moving load. However, for simplicity, a planar model (two-dimensional model) was used as a substitution. The anisotropic property of the structure layers was approximated as transverse isotropy. Both the interlayer conditions (bonded and sliding) between the adjacent layers and load properties including load velocity and frequency were considered in the mathematical derivation of the analytical solution. Following the mathematical derivation, implementation and verification, the analytical solutions obtained were able to successfully evaluate the mechanical behaviors of an anisotropic elastic multi-layered medium subjected to a moving load. Subsequent numerical results revealed that both the anisotropic properties and the interlayer conditions have a significant impact upon the mechanical behaviors of an elastic multi-layered medium. In contrast, due to the conditions/assumptions considered in the computations, the load velocity and frequency were found to have a negligible impact on the mechanical behavior.